2019
DOI: 10.1021/acs.jmedchem.9b01856
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Selective Fluorescent Ligands as Pharmacological Research Tools for the Human Adenosine A2A Receptor

Abstract: Among class A G protein-coupled receptors (GPCR), the human adenosine A 2A receptor (hA 2A AR) remains an attractive drug target. However, translation of A 2A AR ligands into the clinic has proved challenging and an improved understanding of A 2A AR pharmacology could promote development of more efficacious therapies. Subtype-selective fluorescent probes would allow detailed realtime pharmacological investigations both in vitro and in vivo. In the present study, two families of fluorescent probes were designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 61 publications
3
28
0
Order By: Relevance
“…From molecular docking studies, the researchers suggested that the fluorescent AlexaFluor® 488 moiety present in MRS7416 is binding to the hydrophilic extracellular loops of the receptor. This would make the probe essentially “bitopic,” i.e., bridging two separate domains of the hA 2A R. Very recently, the toolbox was expanded with a series of preladenant-based ligands equipped with a range of fluorophores [ 94 ]. These compounds showed p K D values between 7.1 and 7.8 and were highly A 2A -selective with practically no binding to the other adenosine receptor subtypes.…”
Section: Fluorescent Probesmentioning
confidence: 99%
“…From molecular docking studies, the researchers suggested that the fluorescent AlexaFluor® 488 moiety present in MRS7416 is binding to the hydrophilic extracellular loops of the receptor. This would make the probe essentially “bitopic,” i.e., bridging two separate domains of the hA 2A R. Very recently, the toolbox was expanded with a series of preladenant-based ligands equipped with a range of fluorophores [ 94 ]. These compounds showed p K D values between 7.1 and 7.8 and were highly A 2A -selective with practically no binding to the other adenosine receptor subtypes.…”
Section: Fluorescent Probesmentioning
confidence: 99%
“…If required, a further increase in chemical reactivity was envisaged by incorporating more fluorine atoms onto the phenyl ring. Based on recent fluorescent antagonists 10 and the selective A 2A R antagonist ZM241385 11 we designed such a ligand, 1 (Figure 1b, Supplementary Figure 1), and used molecular modelling to guide close proximity of the phenyl ester with a nucleophilic amino acid side chain to allow transfer of a Cy5 fluorophore to the receptor (Figure 1a,b Supplementary Figure 2). To test its labelling efficacy in an over-expression system, we added increasing concentrations of 1 to membranes prepared from HEK293 cells expressing SNAP-A 2A R labelled with Lumi4-Tb and measured time-resolved fluorescence resonance energy transfer (TR-FRET) between Lumi4-Tb and the Cy5 subsequently attached to the receptor by 1 via ligand-directed covalent labelling.…”
Section: Figurementioning
confidence: 99%
“…The construct pcDNA4TO-TwinStrep(TS)-SNAP-β2AR was generated by amplification of the SNAP and β2AR sequences of the pSNAPf-ADRB2 plasmid (NEB) and insertion into pcDNA4TO-TS using Gibson assembly (Heydenreich, Miljus et al 2017). The construct pcDNA4TO-TS-SNAP-A2A was generated by amplifying the A2A receptor from the pDNA3.1 SNAP A2A construct described in (Comeo, Kindon et al 2020) and inserting into pcDNA4TO-TS-SNAP vector using Gibson assembly. This therefore gave the construct pcDNA4TO-TS-SNAP-A2A.…”
Section: Molecular Biologymentioning
confidence: 99%